A longitudinal study of the commitment to business ethics of corporate Australia. (6th March 2008) - Callaghan, Michael; Wood, Greg; Svensson, Goran
This paper compares the results of a longitudinal study of ten years, conducted at five yearly intervals, from 1995 to 2005. The aim of the study was to examine the commitment to business ethics of the top 500 Australian companies. Primary data was obtained via a self-administered mail questionnaire distributed to a census of the top 500 Australian companies. This paper examines those responses that indicated that their company possessed a code of ethics. The paper finds that business ethics has continued to evolve and that, in most cases, such evolution has been positive. It would seem that codes of ethics have moved beyond a regulatory requirement and are now considered an integral component of corporate culture and commercial practice in many of Australia's top companies.